2021
DOI: 10.3390/diagnostics11020364
|View full text |Cite
|
Sign up to set email alerts
|

Motor Pathophysiology Related to Dyspnea in COPD Evaluated by Cardiopulmonary Exercise Testing

Abstract: In chronic obstructive pulmonary disease (COPD), exertional dyspnea, which increases with the disease’s progression, reduces exercise tolerance and limits physical activity, leading to a worsening prognosis. It is necessary to understand the diverse mechanisms of dyspnea and take appropriate measures to reduce exertional dyspnea, as COPD is a systemic disease with various comorbidities. A treatment focusing on the motor pathophysiology related to dyspnea may lead to improvements such as reducing dynamic lung h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…In patients with HF or PAH, excess ventilation often occurs with a rapid shallow breathing pattern, to compensate for the exertional pathophysiological condition, which has been postulated to be due to (1) earlier onset of exertional lactic acidosis, (2) increased chemoreflex activity, (3) a restrictive lung mechanism, (4) reduction in alveolar-capillary gas diffusion, and (5) increased sympathetic activity (Sue, 2011 ). In humans, regardless of the underlying disease, pH-related homeostasis is commonly an important metabolic determinant of ventilatory control during exercise (Miki et al, 2009 , 2012 , 2013 ; Wasserman et al, 2014 ; Miki, 2021 ). Näveri et al reported that the main limiting factor of exercise performance in both healthy subjects and HF patients is the development of lactic acidosis, although it occurs at different levels of exercise (Näveri et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with HF or PAH, excess ventilation often occurs with a rapid shallow breathing pattern, to compensate for the exertional pathophysiological condition, which has been postulated to be due to (1) earlier onset of exertional lactic acidosis, (2) increased chemoreflex activity, (3) a restrictive lung mechanism, (4) reduction in alveolar-capillary gas diffusion, and (5) increased sympathetic activity (Sue, 2011 ). In humans, regardless of the underlying disease, pH-related homeostasis is commonly an important metabolic determinant of ventilatory control during exercise (Miki et al, 2009 , 2012 , 2013 ; Wasserman et al, 2014 ; Miki, 2021 ). Näveri et al reported that the main limiting factor of exercise performance in both healthy subjects and HF patients is the development of lactic acidosis, although it occurs at different levels of exercise (Näveri et al, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence by Bruce et al suggests that abnormal peripheral muscle metaboreflexes are responsible for the excess ventilation in COPD patients (Bruce et al, 2016 ). In cardiopulmonary diseases, identification of not only cardiopulmonary responses but also the peripheral muscle condition is commonly useful to facilitate personalized care based on each individual's dysfunction (Shelton et al, 2010 ; Vogiatzis and Zakynthinos, 2013 ; Maekura et al, 2015 ; Miki, 2021 ). In advanced COPD, measurement of ΔFO 2 might be informative for identifying ventilatory inefficiency, and might be a compensatory component for O 2 availability in the body's cardiopulmonary and peripheral muscle crosstalk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that AT and peak oxygen uptake in patients with CHD were significantly lower than in those without CHD [30]. CPET can detect the cardiopulmonary function reserve and the degree of functional impairment of patients and help understand the gas exchange rate of patients [31]. The worse the cardiopulmonary function is, the worse the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2018, chronic obstructive pulmonary disease (COPD) has become the world's third leading cause of death [1]. The most frequent and intractable problem in patients with COPD is exercise intolerance due to wasted ventilation [2][3][4][5], which leads to poor disease prognosis [6]. Although several measures have been attempted to improve exercise tolerance, they remain insufficient.…”
Section: Introductionmentioning
confidence: 99%